Alternative Dual Exchange Market Regimes : Some Steady State Comparisons - Lizondo, Jose Saul (IMF Working Papers; Working Paper ;, 1990)
This paper compares two alternative dual exchange market regimes. In one of them, the official market clears through changes in international reserves, while in the other regime, the central bank implements a rationing scheme so as to keep international reserves constant. The paper discusses the effects on the rate of inflation, the balance of payments, the real exchange rate, and the spread between the free and the official exchange rate, of various economic policies, including exchange rate policy, fiscal policy, and unification of the exchange markets. It concludes that the steady state effects for most of these policies are qualitatively the same under both regimes.